Financial hardship and mental health among cancer survivors during the COVID-19 pandemic: An analysis of the US COVID-19 Household Impact Survey - Islam, Jessica Y.; Turner, Kea; Saeb, Huda; Powell, Margaux; Dean, Lorraine T.; Camacho-Rivera, Marlene (Frontiers in Public Health, 2022)
Purpose: Our objective was to (1) identify determinants of financial hardship (FH), and (2) evaluate associations of FH with mental health symptoms among cancer survivors during the COVID-19 pandemic. Methods: Using data from the nationally-representative COVID-19 Impact Survey, we defined cancer survivors as a self-reported diagnosis of cancer(n=854,7.6%). We defined FH using the following question:“ Based on your current financial situation, how would you pay for an unexpected 400 expense?” Multivariable Poisson regression was used to estimate adjusted prevalence ratios (aPR) with 95% confidence intervals(95%CI) to identify determinants of FH and associations of FH with mental health symptoms among cancer survivors overall and by age(18-59 years/60+ years). Results: Forty-one percent of cancer survivors reported FH, with 58% in 18-59 and 33% in 60+ year old respondents. Compared to cancer survivors aged 60+ years, those aged 30-44(aPR:1.74,95% CI:1.35-2.24), and 45-59 years (aPR:1.60,95% CI:1.27-1.99) were more likely to report FH. Compared to NH-White cancer survivors, NH-Black cancer survivors had a 56% higher prevalence of FH (aPR:1.56; 95% CI: 1.23-1.97). Among 60+ years aged cancer survivors, NH-Black (aPR:1.80; 95% CI: 1.32-2.45) and NH-Asian cancer survivors (aPR:10.70,95% CI:5.6-20.7) were more likely to experience FH compared to their NH-White counterparts. FH was associated with feeling anxious (aPR:1.51,95% CI:1.11-2.05), depressed (aPR:1.66,95% CI:1.25-2.22), and hopeless (aPR:1.84,95% CI:1.38-2.44). Conclusion: Minoritized communities, younger adults, and cancer survivors with low socioeconomic status had a higher burden of FH, which was associated with feelings of anxiety, depression, and hopelessness.